2022
DOI: 10.1002/adma.202109083
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanostructured TiO2 in UV Photodetectors: A Review

Abstract: moderate UV light is beneficial for human health, however, excessive UV radiation can cause various human diseases as well as strong destruction to the output of crops and the lifespan of buildings. [1b,3a,4] Therefore, an efficient detection of UV radiation is of significant importance in widespread applications, for example, chemical, environmental, and biological analysis or warning, astronomical investigation, and optical communication. [1c,5] For forewarning UV radiation with high-efficiency, a wide v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
116
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(147 citation statements)
references
References 346 publications
(472 reference statements)
0
116
0
Order By: Relevance
“…Chemosensors 2022, 10, x FOR PEER REVIEW 5 of 13 The optical properties of pure TiO 2 and nPPy-TiO 2 nanocomposites were then characterized by UV-Vis absorption spectra and a photoluminescence spectrum. As shown in Figure 5a, pure TiO 2 displayed an absorption edge around 420 nm, implying a band gap of 3.0 eV of rutile TiO 2 [33]. The absorption edges of nPPy-TiO 2 nanocomposites were around 410 nm, which suggested that PPy changed the band gap of the prepared TiO 2 .…”
Section: Structural and Optical Properties Of The Ppy-tio 2 Nanocompo...mentioning
confidence: 93%
“…Chemosensors 2022, 10, x FOR PEER REVIEW 5 of 13 The optical properties of pure TiO 2 and nPPy-TiO 2 nanocomposites were then characterized by UV-Vis absorption spectra and a photoluminescence spectrum. As shown in Figure 5a, pure TiO 2 displayed an absorption edge around 420 nm, implying a band gap of 3.0 eV of rutile TiO 2 [33]. The absorption edges of nPPy-TiO 2 nanocomposites were around 410 nm, which suggested that PPy changed the band gap of the prepared TiO 2 .…”
Section: Structural and Optical Properties Of The Ppy-tio 2 Nanocompo...mentioning
confidence: 93%
“…An ultraviolet (UV) photodetector is a kind of photo-electronic device that converts a light signal to an electrical signal by using the photoelectric effect of semiconductors. As an important device for both military and civil use, ultraviolet (UV) photodetectors have attracted much attention in recent years because of their vast applications in military early warning, communication sensing, environmental monitoring, disease diagnosis, and so on [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Because UV radiation is generally divided into three bands (UVA: 320–400 nm, UVB: 280–320 nm, and UVC: 10–280 nm) according to the standards of the International Commission on Illumination [ 11 ], over the past two decades, wide-bandgap inorganic semiconductors (such as ZnO, TiO 2 , SnO 2 , ZnS, GaN, Ga 2 O 3 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…11 Owing to their facile miniaturized integration along with their strong radiation response to harsh environment sustainability, wide band gap (E g ) semiconductors have turned out to be potential candidates. 12 Among the various semiconductors with a wide E g , such as ZnS, 13,14 TiO 2 , 15,16 GaN, 17 SiC, 18 ZnSe, 19 ZnTe, 20 In 2 Te 3 , 21 MoS 2 , [22][23][24] Nb 2 O 5 , 25,26 ZnO, 27 NiO, 28,29 SnO 2 , [30][31][32] K 2 Nb 8 O 21 , 33 etc., which have been studied for UV PD applications, zinc oxide (ZnO, E g E 3.37 eV) has attracted huge attention due to its large room-temperature (RT) excitonic binding energy (B60 meV), low collision ionization coefficient, environmentally stable chemical and radiation properties, and so on. [34][35][36] ZnO has thus been the champion material for UV detection with extensive research over time.…”
Section: Introductionmentioning
confidence: 99%